Implementasi Kebijakan Bantuan Pangan Non Tunai (BPNT) di Kecamatan Muara Bangkahulu Kota Bengkulu - Feny Sahara; Faizal Anwar; Titi Darmi (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2022)
The distribution of Non-Cash Food Aid (BPNT) by the Bengkulu City Government aims to fulfill basic food needs for the underprivileged, but there are problems encountered in the field such as inaccuracy of targets in distribution and the distribution is not timely. Researchers are interested in investigating more deeply how the implementation of the Non-Cash Food Assistance (BPNT) policy and what are the obstacles in implementing the NonCash Food Assistance (BPNT) policy in Muara Bangkahulu District, Bengkulu City. The research method used in this research is descriptive qualitative research method. The results of the research regarding the implementation of the Non-Cash Food Assistance (BPNT) policy in Muara Bangkahulu District are (1) Interorganizational communication carried out by the implementers, namely starting before the launch of the Non-Cash Food Assistance (BPNT) program through e-Warong in Muara Bangkahulu District has been implemented well, (2) the characteristics of implementers in the process of implementing BPNT policies through e-Warong in Muara Bangkahulu District in providing services to KPMs are in accordance with existing procedures, (3) Social, Economic and Political conditions in the distribution of BPNT in Muara Bangkahulu District has been good in the process of distributing BPNT, and (4) The disposition or attitude of the implementers of the parties in the implementation of the NonCash Food Assistance Policy (BPNT) has been realized quite well to the community in Muara Bangkahulu District so that the Implementation of the NonCash Food Assistance Policy (BPNT) is running in accordance with applicable regulations and Alan effectively.